Pengembangan Aplikasi Manajemen Perencanaan Bahan Baku Dan Pemesanan Pada Konveksi Sablon Malang - Fakhruzzahid Wahdah; Bayu Priyambadha; Denny Sagita Rusdianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Sablon Malang is one of the examples of convection and screen printing business operates 24 hours per day, even more sablon malang split production layout apart from each other. Place the store sablon malang, production of the convection, and the production of screen printing process so that separate orders require time and effort for the workers. Sablon Malang in the record-keeping of raw materials also still using manuals so that the order in the machining process occurs frequently run out of raw materials which resulted in an order to be late. Overcoming these problems made the raw material management system and bookings are expected to facilitate and monitor all activities of the production process. This system uses the method Requirement Material Planning for the create all machining process both raw materials as well as the booking process. This research starts from the needs analysis system that is carried out by means of direct observation and interviews in Sablon Malang. Then done done stage design which contained the design architecture, designing interfaces, designing data structures and designing components while the implementation phase will implement all of the design already made, both performed with the Object Oriented approach. Testing phase using Unit testing, Non Functional Testing, and Validation Testing.The results of testing valid percentage i.e. 100%.